Prevalence of abnormal Pap smear in pregnant women - Banerjee, Kakoli Nikhil; Rani, Poonam; Chandra, Mukul; Khan H., Fayaz (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Background: Cervical cancer is a leading cause of morbidity and mortality among women, particularly in low-resource settings. Pregnancy presents an opportunity for early cervical screening, yet routine screening programs remain inadequate. This study aims to determine the prevalence of abnormal Pap smears in pregnant women and assess the association of abnormal findings with age and clinicodemographic characteristics. Methods: This cross-sectional study was conducted at the Department of Obstetrics and Gynaecology, F.H. Medical College and Hospital, Agra. A total of 197 pregnant women undergoing routine antenatal Pap smear screening were enrolled. Cytological evaluation was performed using the Bethesda classification system. Statistical analysis was conducted using SPSS version 26, with chi-square tests applied to determine associations between variables. Results: Among 197 participants, 73.1% had normal or inflammatory smears, while 26.9% had varying degrees of epithelial abnormalities. The prevalence of ASCUS, Low SIL and High SIL were 10.7%, 8.6% and 7.6%, respectively. No cases of squamous cell carcinoma were identified. Women aged 30-40 years exhibited the highest proportion of abnormal Pap smears (49%). Rural residence, lower socioeconomic status and multiparity were associated with increased prevalence of abnormal cytology, though age was not statistically significant as a risk factor. Conclusions: The study highlights a significant proportion of abnormal Pap smears among pregnant women, underscoring the importance of integrating cervical cancer screening into routine antenatal care. Awareness programs, early HPV vaccination and improved access to gynecological services are essential strategies for reducing the burden of cervical cancer in pregnant populations.